Stability of berm type breakwater with cube blocks in the lower slope and berm. (1st December 2020) - Yuksel, Yalcin; Cevik, Esin; van Gent, Marcel R.A.; Sahin, Cihan; Altunsu, Ahmet; Tugce Yuksel, Z.
Abstract: In this study, the stability of cube armour units in the lower slope and berm of rubble mound breakwaters with a berm was investigated for irregular and regular placement methods. Cubes are simple and cheap in production. However, the design conditions for the upper slope and lower slope may differ depending on the water level of the dominant storm conditions. For the upper slope, relatively higher water levels are dominant. The berm has a reducing effect on the wave loading on the upper slope and therefore, it may be relevant to use cubes in the lower slope, in combination with rock in the upper slope. In this study, a regular placement technique named "the double pyramid placement method" was applied for cubes placed on the lower slope and the berm. This placement technique was compared with the irregular placement technique by performing experiments in a wave flume. As a result of this investigation, the regular placement method was found to be superior for the stability of cubes in the lower slope and berm of rubble mound breakwaters with a berm. Highlights: This study presents the stability of cubes which were placed in the lower slope and berm using two different placement methods as irregular and regular placements. This study is the state of art investigation for the stability of concrete armour units in the lower slope and berm. As a result of this investigation, the regular placement method was also found to be superior for the stability of cubes in the lower slope and berm of rubble mound breakwaters with a berm. New stability formulae are introduced including the influence of the berm width and the berm level.